Estudio de factibilidad para la creación de una empresa especializada en el servicio de limpieza de hogares, locales comerciales e instituciones en el cantón Valencia - Villarroel Molina, Lisbeth Roxana (2014)
The present study entitled "Feasibility study for the creation of a company specializing in home cleaning service, commercial and institutions in the canton valence." Is based on the urgent need to support the social sector from the perspective of seeking order and cleanliness of their homes, places of work etc. Seeking to answer several questions, posed the following research question How does the lack of a company specializing in the cleaning service affects the level of cleanliness in homes, commercial and public and private institutions of the canton Valencia? This led us to propose the following objectives;  Investigate the acceptance would have the cleaning service company in the community of Valencia.  Determine that the public costs of Valencia would be willing to pay for the cleaning service in homes, commercial and institutional Valencia Canton.  Develop a proposal to determine the creation of a joint household cleaning services, commercial premises in the canton Valencia. The assumptions underlying this research are: General Hypothesis" The feasibility study for the creation of a company providing cleaning services in homes, commercial and institutions will be well received by the community of Canton Valencia? For the preparation of the framework were taken as reference the main variables of hypotheses such as association, organizations, market research, investment plan, strategic analysis, and so on. In terms of methodology, analytical methods were applied, inductive, deductive and type of field research and literature was, we conducted a survey, and applying a statistical formulation resulted threw us to survey 347 people. Among the most relevant results we can mention that 100% of respondents whether they agree with the creation of a new company that provides excellent services and quality.